Review of the 21st Century Truck Partnership : second report (National Academies Press, 2012)
In July 2010, the National Research Council (NRC) appointed the Committee to Review the 21st Century Truck Partnership, Phase 2, to conduct an independent review of the 21st Century Truck Partnership (21CTP). The 21CTP is a cooperative research and development (R & D) partnership including four federal agencies-the U.S. Department of Energy (DOE), U.S. Department of Transportation (DOT), U.S. Department of Defense (DOD), and the U.S. Environmental Protection Agency (EPA)-and 15 industrial partners. The purpose of this Partnership is to reduce fuel consumption and emissions, increase heavy-duty vehicle safety, and support research, development, and demonstration to initiate commercially viable products and systems. This is the NRC's second report on the topic and it includes the committee's review of the Partnership as a whole, its major areas of focus, 21CTP's management and priority setting, efficient operations, and the new SuperTruck program.